Diagnostic challenges in differentiating mediastinal tuberculosis from mediastinal tumors: A case report - Aida; Noni Novisari Soeroso; Herani Mutia Riandini (Respiratory Medicine Case Reports)
Mediastinal tuberculosis poses significant diagnostic challenges due to its nonspecific clinical and radiological features, particularly in high TB incidence regions like Indonesia. Here, we present the case of A 17-year-old male, initially diagnosed with a mediastinal tumor, was later confirmed to have mediastinal tuberculosis (TB). Despite normal lab results, imaging revealed a right parahilar mass. Bronchoscopy indicated bronchial stenosis, and VATS converted to thoracotomy confirmed TB. The patient improved significantly after six months of anti-tuberculosis therapy (ATT). Managing mediastinal tumors and tuberculosis requires tailored surgical interventions like thoracotomy or VATS, emphasizing the need for accurate preoperative diagnoses. This case underscores the importance of comprehensive diagnostic evaluation, including histopathological and microbiological tests, to distinguish TB from other mediastinal pathologies and ensure appropriate treatment.